Clinical perspectives on placenta accreta spectrum: a case series - Rajeswari, K. S. Raja; Parthiban, Pavithraa; Vidhyantha, Kiruba Hannah (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
To describe the presentation and management of three cases of placenta accreta spectrum. Placenta accreta spectrum (PAS), first described in 1937, refers to the pathological invasion of placental trophoblasts into the myometrium and beyond. While a strong association exists between PAS and uterine scarring-often attributed to defective decidualization at the endometrium-myometrium interface-this does not fully explain all cases. Here we report three cases of placenta accreta spectrum disorders, two cases with placenta accreta and one with placenta percreta. Emergency LSCS was performed for two patients with placenta accreta and emergency laparotomy proceeded to subtotal hysterectomy was done for placenta percreta. These patients had a stormy post operative period and required multidisciplinary approach for management. In our study, all three cases experienced spontaneous bleeding far from term and required a high index of suspicion for early diagnosis and effective treatment. With rise in Caesarean sections, placenta accreta spectrum disorders are not uncommon in today’s clinical practice. The treatment option should be individualised and hysterectomy is not the only definitive treatment.